Immunological Features of Neuroblastoma Amplified Sequence Deficiency: Report of the First Case Identified Through Newborn Screening for Primary Immunodeficiency and Review of the Literature - Ricci, Silvia; Lodi, Lorenzo; Serranti, Daniele; Moroni, Marco; Belli, Gilda; Mancano, Giorgia; La Barbera, Andrea; Forzano, Giulia; Mangone, Giusi; Indolfi, Giuseppe; Azzari, Chiara (Frontiers in Immunology, 2019)
This is the first case of NBAS disease detected by NBS for primary immunodeficiency. NBS with KRECs is revealing unknown potentialities detecting conditions that benefit from early recognition like NBAS deficiency. Immune phenotyping should be mandatory in patients with NBAS deficiency since they can exhibit severe immunodeficiency with hypogammaglobulinemia as the most frequent finding. Fever during infections is a known trigger of acute liver failure in this syndrome, so immune dysfunction, should never go unnoticed in NBAS deficiency in order to start adequate therapy and prophylaxis.